2023
DOI: 10.1186/s12888-023-05143-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of web-based educational interventions on mental health literacy, stigma and help-seeking intentions/attitudes in young people: systematic review and meta-analysis

Abouzar Nazari,
Gholamreza Garmaroudi,
Abbas Rahimi Foroushani
et al.

Abstract: Objectives This study aims to provide a systematic review and meta-analysis of the literature on The Effect of Web-Based Educational Interventions on Mental Health Literacy, Stigma and Help-seeking intentions/attitudes in young people. Methods Articles in English published between April 1975 and February 2023 were retrieved from seven databases, leading to a total of 2023 articles identified. Results 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…As a result, although help-seeking interventions commonly focus on mental health literacy (Xu et al, 2018), such interventions for these individuals could also benefit from components aimed at enhancing self- and other compassion, which are positively related to agreeableness (Di Fabio & Saklofske, 2021). This type of nuanced approach to help-seeking interventions might address why a recent systematic review and meta-analysis found that, although interventions targeting mental health literacy improved mental health literacy, they did not improve help-seeking stigmas or attitudes (Nazari et al, 2023). Another example of how personality data could inform help-seeking interventions is that individuals lower in extraversion, despite having high mental health literacy, may still not intend to seek help for mental health concerns due to the inherently social aspect of help seeking.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, although help-seeking interventions commonly focus on mental health literacy (Xu et al, 2018), such interventions for these individuals could also benefit from components aimed at enhancing self- and other compassion, which are positively related to agreeableness (Di Fabio & Saklofske, 2021). This type of nuanced approach to help-seeking interventions might address why a recent systematic review and meta-analysis found that, although interventions targeting mental health literacy improved mental health literacy, they did not improve help-seeking stigmas or attitudes (Nazari et al, 2023). Another example of how personality data could inform help-seeking interventions is that individuals lower in extraversion, despite having high mental health literacy, may still not intend to seek help for mental health concerns due to the inherently social aspect of help seeking.…”
Section: Discussionmentioning
confidence: 99%